A Coal Burst Mitigation Strategy for Tailgate during Deep Mining of Inclined Longwall Top Coal Caving Panels at Huafeng Coal Mine - Guorui Feng; Pengfei Wang; Yoginder P. Chugh; Jingli Zhao; Zhiqiang Wang; Zhipeng Zhang (Shock and Vibration)
A coal burst mitigation strategy for tailgate in mining of deep inclined longwall panels with top coal caving at Huafeng Coal Mine is presented in this paper. Field data showed that coal bursts, rib sloughing or slabbing, large convergence, and so forth frequently occurred within the tailgate entries during development and panel retreating employing standard longwall top coal caving (LTCC) layout which resulted in fatal injuries and tremendous profit loss. The contributing factors leading to coal bursts were analyzed. Laboratory tests, in situ measurement, and field observation demonstrate that the intrinsic bursting proneness of the coal seam and immediate roof stratum, deep cover, overlying ultrathick (500–800 m) conglomerate strata, faults, and, most importantly, improper panel layout led to coal bursts. By employing a new strategy, that is, longwall mining with split-level gateroads (LMSG), gateroads on either end of a LMSG panel are located at different levels within a coal seam, adjacent LMSG panels overlap end to end, and the tailgate of the adjacent new LMSG panel can be located below the headgate entry of the previous LMSG panel or may be offset horizontally with respect to it. Numerical modeling was carried out to investigate the stress distribution and yield zone development within surrounding rock mass which was validated by field investigation. The results indicate that standard LTCC system gave rise to high ground pressure around tailgate entries next to the gob, while LMSG tailgate entry below the gob edge was in a destressed environment. Therefore, coal bursts are significantly mitigated. Field practice of LMSG at Huafeng Coal Mine demonstrates how the new strategy effectively dealt with coal burst problems in mining of deep inclined longwall panels with a reduced incidence of ground control problems. The new strategy can potentially be applied in similar settings.